The ideal of diversity in organizations - Levine, David P. (2003)
This article offers a psychodynamic exploration of the organizational commitment to diversity. Based on a brief review of organizational rhetoric, two themes are identified. The first is the denial of hatred, which is argued to express the operation of a fantasy of the organization as the peaceable kingdom. This fantasy imagines the organization as a home for those with strong originary group identifications, while refusing to consider how attachment to group identity can foster hate and exclusion. The second theme is the equation of knowledge useful to the organization with life experience connected to group identity. The emphasis in the rhetoric of diversity on the value of experience is linked to a strategy for coping with loss that seeks to make the experience of loss a source of strength. The importance of acknowledging the reality of hate and of coping with, rather than denying, the consequences of loss is emphasized. - Reproduced.
Keywords: Organizations